Florida's Water Resources - Tara Wade; Tatiana Borisova (EDIS)
The use of water is increasing along with Florida's population. Floridians rely on underground freshwater reserves, called aquifers, to supply our diverse water needs (USGS 2016a). In some Florida regions, this underground freshwater reserve can no longer sustain the growing water demands of the population, while also feeding Florida's rivers, springs, and lakes. With periodic droughts, shortages of freshwater may occur. Drought and water shortages in the state have caused urban planners and policy makers to pay closer attention to water use, water supply development, and water resource management. Florida public opinion surveys show that the majority of Floridians rate water as an issue of top importance for the state (UF/IFAS Center for Public Issues Education 2016). A better understanding of Florida's water resources is a first step toward optimizing current freshwater supply use and ensuring adequate water resources in the future.